A New Rapidly Growing Dome-Shaped Choroidal Lesion in an Eye with Treated Retinoblastoma - Babak Masoomian; Maria Pefkianaki; Fariba Ghassemi; Hamid Riazi-Esfahani (Case Reports in Ophthalmological Medicine)
Background. To describe an extensive untreatable choroidal metastasis by retinoblastoma in the treated patient which was clinically indistinguishable from regular tumor recurrence. Methods. A 24-month-old girl without a family history of retinoblastoma (RB) was discovered to have group C RB in her right eye and group D in her left eye. The patient received 12 cycles of intravenous chemotherapy, intra-arterial chemotherapy (IAC), and intravitreal chemotherapy for the left eye and focal adjuvant therapy (laser thermotherapy and cryotherapy) for both eyes. Six months after the last treatment, fundus examination showed a regressed tumor in both eyes. Ten months after the last treatment, except for in addition to tumor recurrence, rising intraocular pressure was noticed in the left eye. While doing IAC for the left eye, a very rapid growing yellowish dome-shaped mass was found which had doubled in size in two weeks. Enucleation was considered for her. Results. Pathology evaluation of the enucleated eye revealed a very massive dome-shaped choroidal metastasis invasion with poorly differentiated RB tumor. Prophylactic systemic chemotherapy was performed for the patient. Conclusion. Choroidal metastasis in RB patients is often diagnosed based on pathology reports, but it may rarely be seen in clinical examinations especially if the pattern of tumor recurrence and growth is abnormal.